Anti-angiogenic effect of water extract from the fruiting body of Agrocybe aegerita. (January 2017) - Lin, Shaoling; Ching, Lai Tsz; Lam, Kalung; Cheung, Peter C.K.
Abstract: The water extract of the mushroom fruiting body of Agrocybe aegerita ( AaE ) had a total phenolic content of 13.67 ± 0.21 GAE (μM)/mg extract and 5 dominant phenolic acids including gallic acid, protocatechuic acid, chlorogenic acid, ferulic acid and sinapic acid were identified which accounted for 2.5% dry weight of the extract. AaE inhibited the vascular endothelial growth factor (VEGF)-induced proliferation in HUVECs shown by the MTT assay. Down-regulation of intracellular reactive oxygen species (ROS) level and VEGF secretion were also observed in Caco-2 cells treated with AaE . Inhibition of other angiogenic cascades in HUVECs by AaE (at 25 μg/mL) included a decrease in the migration of endothelial cells (ECs) by 46.14 ± 8.53% as evidenced by the wound healing assay and transwell insert assay; as well as a complete blocking of the VEGF-induced formation of capillary network on matrigel matrix. Taken together, these results demonstrated the presence of anti-angiogenic properties of AaE in vitro and among other compounds present in AaE phenolics might contribute to the effect. Therefore, Aa could be considered as potential functional food with antitumor effect modulated by inhibition of angiogenesis. Highlights: The phenolic profile of Agrocybe aegerita water extract was identified and quantified. Agrocybe aegerita extract reduce the intracellular ROS level and suppress the VEGF secretion in Caco-2 cells. Anti-angiogenic activity of Agrocybe aegerita extract was presented for the first time.